ANALISIS EFEK MUSIM HUJAN DAN KEMARAU TERHADAP HARGA BERAS - Kumara Jati (Politeknik APP Jakarta, 2018)
This study analyzes the effects of the rainy and dry seasons on rice prices. Autoregressive and Moving Average (ARMA) and Autoregressive Conditional Heteroskedasticity / Generalized Autoregressive Conditional Heteroskedasticity (ARCH / GARCH) with a dummy variable. We used daily data of the stock and the price of rice from January 29, 2014 until January 29, 2018. ARMA (0,1)-ARCH (1) model with dummy variable that is dry season is more influence conditional variance of rice price compared with rainy season dummy variable. Stakeholders need to pay more attention to fluctuations in rice prices, especially in the dry season because rice supply is relatively less and there is only puso harvest.